Sociodemographic profile of Infertile Women Presenting at Bangabandhu Sheikh Mujib Medical University (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Infertility is a medical as well as a psychological problem of the couples who suffer from it. To serve them efficiently, their sociodemographic profile must be taken into consideration during work up, treatment and counseling.Objective: The objective of the study was to describe and analyze the sociodemographic profile of the infertile women attending Bangabandhu Sheikh Mujib Medical University.Method: Descriptive analysis of data collected and compiled by interviewing the couples attending Infertility outdoor of Bangabandhu Sheikh Mujib Medical University.Results: 64.64% of the women were in the age group 20-29 years. 64.13% of women had 10 or less than 10 years of education. 79.79% of women were housewives.69.69%) of women were from urban areas, with 59.06% from within Dhaka city. 35.35% of the women were from low and 37.37% of the women were from middle socioeconomic condition. One third of women presented with less than three years of infertility. The ratio of primary and secondary infertility is 2:1. Badly managed labour and delivery was the most common cause of secondary infertility.Conclusion: The findings of the study help us understand the needs and abilities of the infertile women presenting to us and decide the best possible strategies of treating and counseling them.J Shaheed Suhrawardy Med Coll, December 2015, Vol.7(2); 63-65